Emotional Content and Source Memory for Language: Impairment in an Incidental Encoding Task - Ferré, Pilar; Comesaña, Montserrat; Guasch, Marc (Frontiers in Psychology, 2019)
Research into the effects of emotion on source memory (i.e., memory for certain contextual details of a stimulus, such as its location, color, or temporal context) has yielded inconsistent findings. Mather and her co-workers tried to account for such inconsistencies by pointing out the relevance of the characteristics of the feature examined. Specifically, they distinguished between intrinsic and extrinsic features (Mather, 2007) and between goal-relevant and goal-irrelevant information (Mather and Sutherland, 2011). In the current study, we investigated source memory for language, which is an intrinsic feature or words. Catalan-Spanish bilinguals were tested in three experiments involving a recognition task in which they were asked about the language of presentation (Catalan or Spanish) of emotional and neutral words. In Experiments 1 and 2, source memory for negative and neutral words was assessed. In Experiment 1 participants performed an intentional encoding task in which language was a goal-relevant feature. In Experiment 2, they did an incidental encoding task in which language was also goal-relevant. Experiment 3 replicated Experiment 2 but negative words were replaced by positive words. The results showed an impairment in source memory for the language of presentation of emotional words when the encoding task was incidental, but not when it was intentional. Such impairment was observed with both negative words and positive words. The results are discussed in relation to the proposals of Mather and co-workers and point to the relevance of modulating factors, such as the intentional/incidental nature of encoding.